Memang Lampung: Discursive Relations of Islam and Local Culture Within The Bark Manuscript No. 2476 - Fauzan Fauzan; Ahmad Isnaeni; Faizal Amin; Bakhtiyor Tursunov (Pascasarjana IAIN Pontianak, 2025)
Studies on Islam in Lampung have thus far provided limited insight into the nature of the relationship between Islam and local culture during the early period of its introduction. This study aims to examine that relationship as represented in Memang (ritual chants) from Lampung. This research employs a qualitative design using a philological approach. The primary data source consists of the transcription and transliteration of a bark-paper manuscript from the Lampung Museum, inventory number 2476. The data are analyzed through the theoretical framework of Islam as a discursive tradition, as articulated by Talal Asad. The findings indicate that Bark Manuscript No. 2476 contains four Memang texts that reflect a discursive relationship between Islam and Lampung culture. This relationship is manifested through five key indicators: (1) the positioning of Islam as a source of sacred legitimacy; (2) the integration of Islamic discourse into local ritual language; (3) the continuity and rearticulation of local cosmology; (4) the construction of a semantic hierarchy within the structure of the Memang texts; and (5) the performativity of ritual language as an operational expression of Islamic discourse. This study concludes that the configuration of Memang texts in Lampung reflects a discursive mode of interaction between Islam and local culture, in which local religious practices operate within Islam as a discursive tradition.